Bioactivity and Toxicity of Senna cana and Senna pendula Extracts - J. A. Monteiro; J. M. Ferreira Júnior; I. R. Oliveira; F. L. A. Batista; C. C. C. Pinto; A. A. S. Silva; S. M. Morais; M. G. V. Silva (Biochemistry Research International)
This work investigated the content of total polyphenolic compounds and flavonoids as well as their toxicity and larvicidal and acetylcholinesterase inhibitory activities. The antioxidant activities of two medicinal Senna species extracts (Senna cana and Senna pendula) were also investigated. The ethanol extract of the leaves of S. cana and the ethanol extract of the branches of S. pendula presented the best performance in the DPPH/FRAP and ABTS/ORAC assays, respectively. For the inhibition of acetylcholinesterase, the hexane extract of the flowers of S. pendula presented the lowest IC50 value among the ethanol extracts of the leaves of S. cana and showed the best performance in some assays. The hexane extract of the leaves of S. pendula and the hexane extract of the branches of S. cana were moderate to Artemia salina Leach. In the quantification of phenols and flavonoids, the ethanol extract of the leaves of S. cana presented the best results. The ethanol extracts of the leaves of S. cana were found to be rich in antioxidants, phenolic compounds, and flavonoids. These results indicate the antioxidant potential of the extracts of Senna species and can be responsible for some of the therapeutic uses of these plants.